In vitro analysis of the marginal adaptation and discrepancy of stainless steel crowns - Riaan Mulder; Rasha Medhat; Nadia Mohamed (Acta Biomaterialia Odontologica Scandinavica)
Aim: The purpose of the study was to assess the marginal adaptation and discrepancy of SSC’s. Differences in adaptation and discrepancy between the four surfaces (mesial, lingual, distal, and buccal) were evaluated. Methods: The placement of stainless steel crowns were completed on a phantom head in accordance with the clinical technique. The ideal tooth preparation was made and this ‘master tooth’ duplicated to achieve a sample size of 15. The stainless steel crowns were placed, trimmed, and cemented as per the clinical technique. The cemented stainless crowns were analyzed under 100× stereomicroscope magnification. The marginal adaptation and discrepancy of each specimen was measured every 2 µm. Results: All the specimens showed marginal adaptation and discrepancy. The lingual margin had a significantly better adaptation (p < .0001) over the other surfaces. The buccal surface was the only surface that had an appropriate supra-CEJ level with a significance of p < .0001. Conclusion: The marginal discrepancies occur during the trimming procedure and assessment of the gingival approximation of the SSC margin. The inspection of stainless steel crown adaptation and discrepancy is an essential clinical step.